Phonological Analysis Of Arabic Diphthongs In Defective Verbs - Mohamad Isa, Abdul Azim; Nordin, Fitri Nurul’ain; Zakaria, Muhamad Zaidi; Amat Suparia, Fariz Azzuan; Mohamed Raffi, Muhammad Syaffiq; Hassan, Abd Rauf (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The Arabic diphthongs have two sounds, which are /aɪ/ and /aʊ/, each in its nouns and weak verbs. This study analyzes phonological rules related to Arabic diphthongs and syllable segmentation among Arabic diphthongs. Qualitative methods are applied in this research, and the content analysis is conducted using Chomsky and Halle’s phonological rules (1968) and Crowley's (1987) theory to analyze all data. The data are collected from the Arabic dictionary called Mu’jam Taşrīf al-`af’āl al-‘arabiyyah and the data are then divided into two categories, namely sound /w/ and /y/. The study observes that the Arabic diphthong sounds are found in nouns and defective verbs with suffixes other than /a/, /t/, and /w/. The study finds that in Arabic, diphthong sounds are deleted in defective verbs when the suffix consists of two phonemes. These sounds transform into long vowel sounds upon adding/a/, indicating the third-person singular male in the past tense. The suffixes /t/ and /w/ similarly convert the diphthong to a primary vowel. This study concludes that phonological changes occur more frequently in Arabic defective verbs than in nouns, following specific rules. Additionally, syllable segments change when the glide sounds forming diphthongs are deleted.